Perbandingan di antara penghasilan model digital tiga dimensi dan model fizikal bagi craniofacial tisu keras - Abdul Majid @ Zakaria, Zakiah (2007)
Accurate measurement on human craniofacial is crucial to surgeon and radiologist for surgical planning. This research focuses on the construction of digital three-dimensional (3D) models for craniofacial using scanned data from Computed Tomography (CT) device. It involves two comparisons to determine the best software to produce digital 3D model and the most accurate measuring method. The digital 3D models were produced using three software namely Rapidform2004, 3D Doctor and 3D Slicer. Then the 3D models which were produced by the three software were compared with a gold standard model produced by Materialise's Interactive Medical Image Control System (MIMICS) software. The comparisons were based on standard deviation, Root Mean Square (RMS), variance and measurement. The results yield the 3D Slicer can produce the best digital 3D model. In order to determine the most accurate measuring method, the measurements on physical model were carried out by using microscribe digitizer, laser scanner and calliper. The results from each method then compared with the close range photogrammetry method based on measurement, standard deviation and RMS. The results show that microscribe digitizer could provide the most accurate measurements. Finally, a comparison between 3D Slicer and microscribe digitizer were carried out. The comparison shows that the measurement values vary between 0.01 mm and 0.97 mm. A digital 3D model and a physical model could be used to determine a measurement point which is difficult to determine by using conventional method. A simple database was developed by using Microsoft Access 2003 to store all the measurements.